2020
DOI: 10.15804/tner.20.61.3.08
|View full text |Cite
|
Sign up to set email alerts
|

Problem Solving in Mathematics and Scientific Reasoning

Abstract: Th e paper describes the results of a study whose aim was to explore correlations among the components of the construct Culture of problem solving (mathematical intelligence, reading comprehension, creativity and ability to use existing knowledge) and six dimensions of Scientifi c reasoning, which was tested by the Lawson's Classroom Test. Th e total of 180 pupils from the Czech Republic aged 14-15 took part in this study. Th e results show that the dimensions proportional reasoning, control of variables and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Research also shows (for example, [10]) the link between science and reading literacy, as reading is a prerequisite for the quality development of some elements of science literacy. The international study PISA (Programme for International Student Assessment), which investigates reading literacy in 15-year-olds in addition to mathematical and science literacy, has shown that Slovak students often performed statistically significantly worse than Czech students in this literacy [1].…”
Section: Discussionmentioning
confidence: 99%
“…Research also shows (for example, [10]) the link between science and reading literacy, as reading is a prerequisite for the quality development of some elements of science literacy. The international study PISA (Programme for International Student Assessment), which investigates reading literacy in 15-year-olds in addition to mathematical and science literacy, has shown that Slovak students often performed statistically significantly worse than Czech students in this literacy [1].…”
Section: Discussionmentioning
confidence: 99%
“…(Bao et al, 2009;Gormally et al, 2012). In (Cihlář et al, 2017), we present the results of a small research conducted among 23 pupils aged 14-15 in the Czech Republic in 2016. The results of this research proved the legitimacy of the idea of exploring mutual relations between individual components of CPS and SR dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this research proved the legitimacy of the idea of exploring mutual relations between individual components of CPS and SR dimensions. This research was then followed up with extensive research in 2017 to describe the dependency between all components of the CPS and the SR dimensions (Cihlář et al, 2020). The objective of the article is to provide a new perspective on the investigation issue based on the data obtained and to answer the question about the relationship between school performance (classification) and the constructs of CPS and SR.…”
Section: Introductionmentioning
confidence: 99%